2020
DOI: 10.1016/j.jvir.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Locoregional Treatment during Immunotherapy with Nivolumab for Hepatocellular Carcinoma: A Retrospective Study of 41 Interventions in 29 Patients

Abstract: Materials and Methods: A single-center retrospective review included 29 patients undergoing 41 LRTs-transarterial chemoembolization or yttrium-90 transarterial radioembolization-60 days before or concurrently with nivolumab. Demographic, clinical, and laboratory values and adverse events were reviewed before and after nivolumab initiation and after each LRT. Treatment response and time to progression were assessed using Modified Response Evaluation Criteria in Solid Tumors. Clinical events, including nivolumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…Similar to the study of Qin et al, the most common AEs in this study was also RCCEP [16]. However, the AEs incidence of grade III or more with camrelizumab seemed to be lower than that with other ICIs [14,15], suggesting that camrelizumab is safe for the treatment of HCC with UP after TACE.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar to the study of Qin et al, the most common AEs in this study was also RCCEP [16]. However, the AEs incidence of grade III or more with camrelizumab seemed to be lower than that with other ICIs [14,15], suggesting that camrelizumab is safe for the treatment of HCC with UP after TACE.…”
Section: Discussionsupporting
confidence: 83%
“…It is reported that TACE can promote tumor-speci c CD8 + T cell response by killing HCC cells and causing the release of tumorassociated antigens [17]. As suggested by the theoretical advantages, both Zhan et al [15] and Marinelli et al [14] demonstrated the e cacy of transarterial embolization combined with ICIs in the treatment of HCC. Similarly, this study also con rmed that TACE combined with ICI was superior to ICI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous observations, several pilot studies have evaluated the possibility of LRTs combined with ICBs in patients with HCC. In a single-center retrospective study, LRTs, including TACE or TARE combined with nivolumab, were tolerated in a small number of patients with intermediate or advanced HCC without deterioration of liver function [ 99 ], indicating that LRTs with ICBs is a safe strategy. In another retrospective study, TARE combined with ICBs was shown to be safe and tolerable [ 100 ].…”
Section: Clinical Studies Of Icbs As An Adjuvant Treatment Following Lrtsmentioning
confidence: 99%
“…Regarding the safety of LRTs combined with immunotherapy, the available data seem to point towards an acceptable safety profile; for example, TARE plus nivolumab showed a similar safety profile when compared to TARE alone [ 195 ], tremelimumab in combination with ablation proved to be safe for the treatment of advanced HCC [ 193 ], no significant adverse reaction was found when combining RFA with cellular immunotherapy in HCC patients [ 194 ].…”
Section: Combination Of Immunotherapy-lrtmentioning
confidence: 99%